Social Justice Fallacies. - Zorrilla, Víctor (Anuario Filosófico, 2025)
The book "Social Justice Fallacies" by Thomas Sowell, published in 2023, analyzes the most common fallacies about social justice and how public policies often harm those they are trying to help. Sowell shows how inequalities are not always due to discrimination and criticizes redistributive policies that do not consider the repercussions. The author also highlights the importance of examining the consequences of public policies and how good intentions can lead to unnecessary suffering.